Efektivitas Pelaksanaan Program Sembako Dalam Pengentasan Kemiskinan di Kecamatan Medan Belawan - Adam Wira Sanjaya; Muhammad Heru Akhmadi (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2022)
Poverty in Indonesia continues to increase, especially since the COVID-19 pandemic. So that it becomes a problem that needs to be solved by the Indonesian government, one of which is with the social assistance of the Basic Food Program. Social assistance programs are programs where local governments provide financial assistance to communities that are not sustainable. The purpose of this study was to determine the effectiveness of the Basic Food Program in alleviating poverty in Medan Belawan District. The research method used is a case study with a qualitative descriptive approach. Data collection techniques used primary and secondary data through in-depth interviews and documentation studies, then document analysis. The sample selection used purposive sampling technique so that several informants were obtained, namely: Medan City Social Service, Regional Coordinator of the Basic Food Program, District Social Workers, E-Warong, Head of Environmental Groups and Beneficiary Families. The results of this study reveal that the implementation of the Basic Food Program is still not effective based on the indicators used, namely resource approach, process approach, and goals approach. Although the Basic Food Program provides convenience for Beneficiary Families, there are still many things that need to be improved to make it more optimal and effective.